Hydrogen embrittlement behavior of high strength bainitic rail steel: Effect of tempering treatment. (November 2018) - Zhang, Yongjian; Xu, Zhibao; Zhao, Xiaoli; Gao, Guhui; Hui, Weijun; Weng, Yuqing
Abstract: The present study was attempted to evaluate the effect of tempering treatment on the hydrogen embrittlement (HE) behavior of a novel bainitic rail steel by using slow strain rate test (SSRT) with notched round bar specimens. The microstructure of the as-hot rolled rail steel mainly consists of granular bainite and 9 vol% martensite. It was found that tempering treatment could increase the HE resistance and decrease the susceptibility to HE of the as-hot rolled bainitic rail steel except at temper embrittlement temperature of 400 °C, and excellent HE properties could be obtained when tempered at 500 °C at less expense of strength and ductility. The enhanced HE properties are ascribed mainly to the gradual decomposition of blocky M/A constituents as well as the tempering of the martensite. It is thus suggested that suitable tempering after hot rolling could be applied to enhance the HE properties as well as to obtain maximum mechanical properties, and thus to guarantee the safety of bainitic steel rails in service. Highlights: Hydrogen embrittlement (HE) of a novel bainitic rail steel was evaluated. Tempering has significant effect on HE behavior of bainitic rail steel. Excellent HE resistance was gained when tempered at 500 °C at less loss of strength. Large blocky M/A island and brittle martensite are detrimental to HE resistance.